Ultralow dielectric loss in Y‐doped SrTiO3 colossal permittivity ceramics via designing defect chemistry. Issue 12 (12th August 2020) - Wang, Bo; Pu, Yongping; Shi, Yu; Guo, Xu; Zhang, Lei; Chang, Liangliang; Li, Jingwei; Li, Run; Ji, Jiamin; Wei, Tianchen
Abstract: Effects of doping of Y and sintering atmosphere on the dielectric properties of Sr1‐1.5 x Y x TiO3 ceramics (SYT, x  = 0‐0.014) were systematically investigated. The SYT14 ( x  = 0.014) ceramic sintered in N2 attains a colossal permittivity (CP, Ɛr  = 28 084@ 1kHz, 27 685@ 2MHz) and an ultralow dielectric loss (tanδ = 0.007@ 1kHz, 0.003@ 2MHz) at room temperature. Because of using of the A‐site deficient, there are V Sr, , in SYT ceramics. Through the comprehensive analysis of dielectric responses, X‐ray photoelectron spectroscopy (XPS), electron paramagnetic resonance (EPR), and complex impedance data, it is proved that doping of Y promotes the formation of Y Sr ∙ (Y 3+ are located at Sr 2+ site), Y Ti, (Y 3+ are located at Ti 4+ site), and Ti 3+, and sintering in reducing atmosphere of N2 results in more V O ∙ ∙ (oxygen vacancy) and V Sr, , (strontium vacancy) generating in SYT ceramics. The defect dipoles, s u c h a s V Sr, , ‐ V O ∙ ∙, T i 4 + ∙ e ‐ V O ∙ ∙ ‐ e ∙ T i 4 +, Y Sr ∙ ‐ e ∙ T i 4 +, 2 Y Sr ∙ ‐ V Sr, , , Y Sr ∙ ‐ Y Ti, , and 2 Y Ti, ‐ V O ∙ ∙ formed by introduced defects make charge carriers localized in SYT ceramics. The combined action of the massive defect dipoles is responsible for the ultralow tanδ and CP in SYT14 ceramics sintered in N2 .